Effect of acute environmental hypoxia on protein metabolism in human skeletal muscle. (25th March 2013) - D'Hulst, G.; Jamart, C.; Van, R.; Hespel, P.; Francaux, M.; Deldicque, L.
Abstract Hypoxia‐induced muscle wasting has been observed in several environmental and pathological conditions. However, the molecular mechanisms behind this loss of muscle mass are far from being completely elucidated, certainly in vivo. When studying the regulation of muscle mass by environmental hypoxia, many confounding factors have to be taken into account, such as decreased protein ingestion, sleep deprivation or reduced physical activity, which make difficult to know whether hypoxia per se causes a reduction in muscle mass. Aim We hypothesized that acute exposure to normobaric hypoxia (11% O2) would repress the activation of the mTOR pathway usually observed after a meal and would activate the proteolytic pathways in skeletal muscle. Methods Fifteen subjects were exposed passively for 4 h to normoxic and hypoxic conditions in a random order after consumption of a light breakfast. A muscle biopsy and a blood sample were taken before, after 1 and 4 h of exposure. Results After 4 h, plasma insulin concentration and the phosphorylation state of PKB and S6K1 in skeletal muscle were higher in hypoxia than in normoxia (P < 0.05). At the same time, Redd1 mRNA level was upregulated (P < 0.05), whilst MAFbx mRNA decreased (P < 0.05) in hypoxia compared with normoxia. Proteasome, cathepsin L and calpain activities were not altered by environmental hypoxia. Conclusion Contrary to our hypothesis and despite an increase in the mRNA level of Redd1, an inhibitor of the mTORC1 pathway, short‐term acute environmental hypoxia induced a higher response of PKB and S6K1 to a meal, which may be due to increased plasma insulin concentration.